2000
DOI: 10.1046/j.1464-410x.2000.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fasting or desmopressin before treatment on the concentration of mitomycin C during intravesical administration

Abstract: Objective To evaluate two methods of reducing the urine output during treatment (the most easily manipulated variable) in patients undergoing intravesical instillation with mitomycin C, where the concentration-time curve also depends upon dose, diluent volume, residual urine volume, and drug absorption and degradation. Patients and methods The study comprised 20 consecutive patients undergoing a course of six weekly instillations of mitomycin C (40 mg in 40 mL for 1 h) for super®cial bladder carcinoma. Urine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…One study has reported the potential benefit, in terms of increasing intravesical drug concentration by reducing urine production, of desmopressin administration prior to mitomycin C treatment. However, data on improvements in actual cytotoxicity were not presented 30. Anthracyclines are weak bases: Epirubicin has a pKa of 7.7; thus, predominantly, it is charged neutrally and is lipophilic at alkaline pH but is charged positively at acid pH.…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported the potential benefit, in terms of increasing intravesical drug concentration by reducing urine production, of desmopressin administration prior to mitomycin C treatment. However, data on improvements in actual cytotoxicity were not presented 30. Anthracyclines are weak bases: Epirubicin has a pKa of 7.7; thus, predominantly, it is charged neutrally and is lipophilic at alkaline pH but is charged positively at acid pH.…”
Section: Discussionmentioning
confidence: 99%
“…A 6-h fasting period prior to instillation, reported to decrease urine volume and prevent 20% of drug dilution, is currently recommended by the European Association Urology guidelines for NMIBC [80]. Cliff and colleagues reported a 38% increase in intravesical mitomycin concentration following the administration of 0.2 mg oral desmopressin 1 h prior to instillation [81]; however, care must be taken in patients with cardiac failure or hyponatremia, and widespread use has not gained acceptance. Alkalinizing the urine with oral bicarbonate has also been shown to improve MMC drug stability, cellular uptake, and muscle penetration [78].…”
Section: Decreasing Urine Production and Urine Alkalinizationmentioning
confidence: 99%
“…pH also affects the antitumor activity, e.g., MMC is more active at acidic pH in monolayer cultures (but no pH dependent-effect in 3-dimensional cultures) ( 69 ), epirubicin is more active at alkaline pH (8.0) than at lower pH (6.0) ( 70 ). The urine production rate and residual urine volume can be altered by patients’ hydration status, e.g., dehydration for 6 hr decreased the average volume of urine production from 209 to 143 ml, which is further reduced to 103 ml by co-administering an antidiuretic desmopressin ( 71 ).…”
Section: Part II Drug Disposition During Intravesical Therapymentioning
confidence: 99%